Dry-method electrode composite binder and preparation method thereof, negative plate and lithium ion battery
By using a composite binder of high-swelling styrene acrylic emulsion and high molecular weight PTFE emulsion, the problems of poor wetting of dry electrodes in the electrolyte and the consumption of lithium ions by PTFE are solved, and more stable battery performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411735804.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The poor wetting ability of the dry electrode in the electrolyte and the consumption of lithium ions by PTFE leads to unstable battery performance and short service life.
A mixture of high-swelling styrene acrylic emulsion and high molecular weight PTFE emulsion was used as a composite binder for the dry electrode. The binder was prepared by co-precipitation technology to improve the wettability of the electrode and reduce the reaction site of PTFE.
It improves the wetting properties of the electrode and the first-time efficiency of the battery, extends the service life of the battery, and improves the performance stability of the battery during circulation.
Smart Images

Figure CN119552594A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery production, and in particular to a dry-process electrode composite binder and a preparation method thereof, a negative electrode sheet, and a lithium-ion battery. Background Art
[0002] For the manufacturing process of lithium battery cells, the key performance of the cells mainly depends on the manufacturing process of the electrode sheets. At present, the manufacturing of electrode sheets is mainly divided into two types: wet method and dry method, and the wet process is the mainstream. The disadvantage of this process method is that toxic and expensive organic solvents such as N, N-dimethylpyrrolidone (NMP) are usually used. During the manufacturing process, NMP will cause the battery to swell during the cycle and the performance will decay too quickly due to excessive water content. In addition, the evaporation and recovery of solvents during the manufacturing process will also cause huge energy consumption. Based on the above problems, the development of solvent-free manufacturing methods for cost-effective and environmentally friendly lithium batteries has important research significance.
[0003] However, there are some urgent problems that need to be solved in dry-process electrodes, such as ① electrolyte wettability: CMC, SBR, PAA, etc. are commonly used binders for traditional wet-process electrodes. The above binders are all soaked and swelled in the electrolyte, especially SBR, which can swell up to 200% or more. Due to the special production requirements of dry-process electrodes, PTFE / modified PTFE must be used as a binder at present, but this binder has excellent chemical resistance, so it is almost insoluble in the electrolyte, which poses great resistance to the subsequent processes of wetness and injection of dry-process batteries; ② PTFE consumption of lithium ions: Since PTFE has slightly poor reduction resistance at low potential, PTFE will lose some active lithium when it reacts with Li and e-electrons during the first cycle of negative electrode lithium insertion.
[0004] The present invention proposes a technical solution for solving the problem of dry electrode. Summary of the invention
[0005] In order to solve the above technical problems, the present invention discloses a dry electrode composite binder and a preparation method thereof, a negative electrode sheet, and a lithium ion battery. The technical solution of the present invention is implemented as follows:
[0006] The first aspect of the present invention provides a dry electrode composite binder, which is a mixture of a high swelling styrene acrylic emulsion and a high molecular weight PTFE emulsion. The high swelling styrene acrylic emulsion has a swelling of greater than or equal to 100% and the high molecular weight PTFE emulsion has a molecular weight of not less than 500W.
[0007] Preferably, the high swelling styrene acrylic emulsion has a melting point of 100° C. to 150° C. and a primary particle size of less than 500 nm; and the high molecular PTFE emulsion has a primary particle size of less than 300 nm.
[0008] The styrene acrylic emulsion of the present invention is prepared by emulsion copolymerization of styrene and acrylate monomers. The acrylate includes at least one of methyl acrylate, ethyl acrylate, butyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate.
[0009] The PTFE emulsion of the present invention is an emulsion aqueous dispersion obtained by polymerizing tetrafluoroethylene monomer in water containing a surfactant.
[0010] The second aspect of the present invention provides a method for preparing a dry electrode composite binder, the preparation method is used to prepare the binder as described in the first aspect of the present invention, the method comprises the following steps:
[0011] S1, adding high swelling styrene acrylic emulsion and high molecular weight PTFE emulsion into a container;
[0012] S2, let stand, then stir;
[0013] S3, the precipitate obtained after solid-liquid separation is dried in a vacuum drying oven to obtain the composite adhesive.
[0014] The mass ratio of the high swelling styrene acrylic emulsion and the high molecular weight PTFE emulsion after solidification in step S1 is (1-10): (90-99).
[0015] The standing time in step S2 is 40 to 80 minutes, the linear speed of the stirring is 0.8 to 1.5 m / s, and the stirring time is 20 to 70 minutes;
[0016] Preferably, the stirring is divided into low-temperature stirring and high-temperature stirring, the low-temperature stirring time is 20 min to 40 min, and the high-temperature stirring time is 30 min to 70 min.
[0017] The low temperature is 5°C to 20°C, and the high temperature is 60°C to 100°C;
[0018] Preferably, the low temperature is selected from 13°C to 17°C, and the high temperature is selected from 80°C to 90°C.
[0019] In step S3, the temperature in the vacuum drying oven is 40° C. to 60° C., and the drying time is 12 h to 36 h.
[0020] The third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet includes the composite binder provided in the first and second aspects of the present invention, and the preparation method of the negative electrode sheet is as follows:
[0021] N1, first add the negative electrode main material and the conductive agent into the planetary stirring tank in a mass ratio of (90-98): (0.5-5);
[0022] The main material of the negative electrode is graphite, and the conductive agent is conductive carbon;
[0023] N2, using a double planetary agitator at a temperature of 10℃~18℃, orbiting at 15r / min~25r / min, rotating at 50r / min~100r / min, stirring for 10min~30min;
[0024] N3, disperse for 30min to 60min to obtain the first mixed material;
[0025] N4, adding a composite binder to the first mixed material;
[0026] The mass ratio of the negative electrode main material to the composite binder is (90-98): (0.5-5);
[0027] N5, maintaining the tank temperature at 10°C to 18°C, stirring for 1h to 2h to obtain the second mixed material;
[0028] N6, placing the second mixed material in an oven at 90°C to 140°C for 1h to 2h;
[0029] N7, the heated second mixed material is placed in a high-speed disperser and dispersed for 4 to 6 minutes, at a line speed of 30 m / s to 45 m / s for fiberization;
[0030] N8, and finally passed through a hot roller pressing mold and composited into a negative electrode sheet.
[0031] The fourth aspect of the present invention provides a lithium-ion battery, which includes the negative electrode sheet provided in the third aspect of the present invention, and also includes a positive electrode sheet, a separator and an electrolyte.
[0032] The advantages of the present invention are as follows:
[0033] The composite binder is prepared by coprecipitation of styrene acrylic + polytetrafluoroethylene (PTFE) emulsion. The material allows high swelling styrene acrylic emulsion and PTFE emulsion to be precipitated into a composite binder by coprecipitation. The high swelling styrene acrylic in the composite material can improve the wettability of the system to a certain extent, and the swelled styrene acrylic may cover part of the PTFE, reduce the PTFE reaction sites, and prevent the loss of part of the active lithium by the reaction of PTFE with Li and e-electrons during the first cycle of negative electrode lithium insertion, thereby improving the first efficiency and making the battery have more stable performance and longer service life in subsequent cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only one embodiment of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] The same parts are denoted by the same reference numerals. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the drawings, and the words "bottom" and "top", "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively.
[0036] Figure 1 This is a SEM picture of the composite adhesive in Example 1 of the present invention; as the only figure of the present invention, this figure is also designated as the abstract figure. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0039] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0040] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0041] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0042] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0043] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0044] There are some urgent problems that need to be solved in dry-process electrodes, such as ① electrolyte wettability: CMC, SBR, PAA, etc. are commonly used binders for traditional wet-process electrodes. The above binders are all soaked and swelled in the electrolyte, especially SBR, which can swell up to 200% or more. Due to the special production requirements of dry-process electrodes, PTFE / modified PTFE must be used as a binder at present, but this binder has excellent chemical resistance, so it is almost insoluble in the electrolyte, which poses great resistance to the subsequent processes of wetness and injection of dry-process batteries; ② PTFE consumption of lithium ions: Since PTFE has slightly poor reduction resistance at low potential, PTFE will lose some active lithium during the first cycle of negative electrode lithium insertion by reacting with Li and e-electrons.
[0045] In order to solve the above problems, the present invention proposes a technical solution to prepare a composite binder by coprecipitation of styrene acrylic + polytetrafluoroethylene (PTFE) emulsion. The material allows high swelling styrene acrylic emulsion and PTFE emulsion to be precipitated into a composite binder by coprecipitation. The high swelling styrene acrylic in the composite material can improve the wettability of the system to a certain extent, and the swelled styrene acrylic may cover part of the PTFE, reduce the PTFE reaction sites, and prevent the loss of part of the active lithium due to the reaction of PTFE with Li and e-electrons during the first cycle of negative electrode lithium insertion, thereby improving the first efficiency and making the battery have more stable performance and longer service life in subsequent cycles.
[0046] The first aspect of the present invention provides a dry electrode composite binder, which is composed of a mixture of a high swelling styrene acrylic emulsion and a high molecular weight PTFE emulsion. The high swelling styrene acrylic emulsion has a swelling of greater than or equal to 100% and the high molecular weight PTFE emulsion has a molecular weight of not less than 500W.
[0047] In some embodiments, the melting point of the high swelling styrene acrylic emulsion is 100° C. to 150° C., and the primary particle size of the emulsion is less than 500 nm; and the primary particle size of the high molecular PTFE emulsion is less than 300 nm.
[0048] In some embodiments, the styrene acrylic emulsion is formed by emulsion copolymerization of styrene and acrylate monomers. The acrylate includes at least one of methyl acrylate, ethyl acrylate, butyl acrylate, methyl 2-methacrylate and ethyl 2-methacrylate.
[0049] The second aspect of the present invention provides a method for preparing a dry electrode composite binder according to the first aspect, the method comprising the following steps:
[0050] S1, adding high swelling styrene acrylic emulsion and high molecular weight PTFE emulsion into a container.
[0051] In step S1, the mass ratio of the high swelling styrene acrylic emulsion to the high molecular weight PTFE emulsion after solidification is (1-10): (90-99).
[0052] In a specific application, the mass ratio of the high swelling styrene acrylic emulsion to the high molecular weight PTFE emulsion after solidification in step S1 can be 1:90, 3:90, 5:90, 9:90, 10:90, 1:91, 1:95, 1:97, 1:99, 2:91, 2:95, 2:97: 2:99, 3:91, 3:95, 3:99, 5:95, 5:99, 7:95, 7:99, 9:95, 9:99, 10:95, 10:99, etc. The above values are only examples, and the present invention does not impose any limitation thereto.
[0053] S2, let stand, then stir.
[0054] The standing time in step S2 is 40 to 80 minutes, and the linear speed of stirring is 0.8 to 1.5 m / s. First, stir at a low temperature of 13 to 17°C for 20 to 40 minutes, then heat to 80 to 90°C and stir for 30 to 70 minutes.
[0055] In specific applications, the standing time in step S2 can be selected to be 40min, 50min, 60min, 70min, 80min, etc.; the linear speed can be selected to be 0.8m / s, 1.0m / s, 1.2m / s, 1.5m / s, etc.; the low temperature can be selected to be 13°C, 14°C, 15°C, 16°C, 17°C, and the stirring time can be selected to be 20min, 30min, 40min, etc.; the heating temperature can be selected to be 80°C, 83°C, 85°C, 88°C, 90°C, etc., and the stirring time can be selected to be 30min, 50min, 60min, 70min, etc.; the above-listed values are only examples, and the present invention does not impose any limitation on this.
[0056] In a specific application, step S2 first needs to be allowed to stand at a low temperature of 13°C to 17°C before low-temperature stirring, and needs to be allowed to stand again for 40min to 80min after high-temperature stirring.
[0057] Furthermore, in step S2, the standing temperature before low-temperature stirring can be selected as 13°C, 14°C, 15°C, 16°C, or 17°C; the standing time after high-temperature stirring can be selected as 40 min, 50 min, 60 min, 70 min, 80 min, etc.; the above-listed values are only examples, and the present invention does not impose any limitation on this.
[0058] S3, the precipitate obtained after solid-liquid separation is dried in a vacuum drying oven to obtain the composite adhesive.
[0059] In step S3, the temperature in the vacuum drying oven is 40° C. to 60° C., and the drying time is 12 h to 36 h.
[0060] In specific applications, the drying temperature of step S3 can be selected to be 40°C, 45°C, 50°C, 55°C, 60°C, etc.; the drying time can be selected to be 12h, 15h, 18h, 21h, 24h, 27h, 30h, 33h, 36h, etc.; the above-listed values are only examples, and the present invention does not impose any limitations on this.
[0061] In a specific application, the solid-liquid separation method in step S3 can be centrifugation or sieving, the centrifugal speed can be set to 3000-8000 r / min, and the sieving can be selected to be 100-300 mesh.
[0062] Furthermore, in step S3, the rotation speed in the centrifuge can be selected as 3000r / min, 4000r / min, 5000r / min, 6000r / min, 7000r / min, 8000r / min, etc.; the sieving mesh number can be selected as 100 mesh, 150 mesh, 200 mesh, etc.; the above-listed values are only examples, and the present invention does not impose any limitation on this.
[0063] The composite binder prepared by the present invention is a styrene acrylic + polytetrafluoroethylene (PTFE) emulsion coprecipitation composite binder. The material allows high swelling styrene acrylic emulsion and PTFE emulsion to be precipitated into a composite binder in the form of coprecipitation. The high swelling styrene acrylic in the composite material can improve the wettability of the system to a certain extent, and the swelled styrene acrylic may cover part of the PTFE, reduce the PTFE reaction sites, and prevent the loss of part of the active lithium due to the reaction of PTFE with Li and e-electrons during the first cycle of negative electrode lithium insertion, thereby improving the first efficiency and making the battery have more stable performance and longer service life in subsequent cycles.
[0064] The third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet includes the composite binder provided in the first and second aspects of the present invention, and the preparation method of the negative electrode sheet is as follows:
[0065] N1, first add the negative electrode main material and the conductive agent into the planetary stirring tank in a mass ratio of (90-98): (0.5-5);
[0066] The main material of the negative electrode is graphite, and the conductive agent is conductive carbon;
[0067] N2, using a double planetary agitator at a temperature of 10℃~18℃, orbiting at 15r / min~25r / min, rotating at 50r / min~100r / min, stirring for 10min~30min;
[0068] N3, disperse for 30min to 60min to obtain the first mixed material;
[0069] N4, adding a composite binder to the first mixed material;
[0070] The mass ratio of the negative electrode main material to the composite binder is (90-98): (0.5-5);
[0071] N5, maintaining the tank temperature at 10°C to 18°C, stirring for 1h to 2h to obtain the second mixed material;
[0072] N6, placing the second mixed material in an oven at 90°C to 140°C for 1h to 2h;
[0073] N7, the heated second mixed material is placed in a high-speed disperser and dispersed for 4 to 6 minutes, at a line speed of 30 m / s to 45 m / s for fiberization;
[0074] N8, and finally passed through a hot roller pressing mold and composited into a negative electrode sheet.
[0075] In specific applications, the mass ratio of the negative electrode main material to the conductive agent in step N1 can be selected from 90:0.5, 90:1, 90:2, 90:3, 90:4, 90:5, 92:1, 92:3, 92:5, 95:1, 95:5, 98:2, 98:3, etc.; the above numerical ratios are only examples and are not limited.
[0076] In specific applications, the stirring temperature in step N2 can be selected from 10°C, 12°C, 14°C, 16°C, 18°C, etc.; the revolution speed can be selected from 15r / min, 18r / min, 20r / min, 23r / min, 25r / min, etc.; the rotation speed can be selected from 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, etc.; the stirring time can be selected from 10min, 15min, 20min, 25min, 30min, etc. The above listed values are only examples, and the present invention does not impose any limitation on this.
[0077] In a specific application, the dispersion time of step N3 can be selected to be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc. The above values are only examples, and the present invention does not impose any limitation thereto.
[0078] In specific applications, the mass ratio of the negative electrode main material to the composite binder in step N4 can be 90:0.5, 90:1, 90:2, 90:3, 90:4, 90:5, 92:1, 92:3, 92:5, 95:1, 95:5, 98:2, 98:3, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.
[0079] In specific applications, the tank temperature in step N5 can be maintained at 10°C, 12°C, 14°C, 16°C, 18°C, etc.; the stirring time can be 1h, 1.2h, 1.5h, 1.8h, 2h, etc. The above values are only examples, and the present invention does not impose any limitation thereto.
[0080] In specific applications, the oven temperature in step N6 can be 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., etc.; the holding time can be 1 h, 1.2 h, 1.5 h, 1.8 h, 2 h, etc. The above values are only examples, and the present invention does not impose any limitation thereto.
[0081] In specific applications, the dispersion time of the high-speed disperser in step N7 can be selected to be 4 min, 5 min, 6 min, etc.; the line speed can be selected to be 30 m / s, 32 m / s, 35 m / s, 38 m / s, 40 m / s, 42 m / s, 45 m / s, etc.; the above values are only examples, and the present invention does not impose any limitations on this.
[0082] Fibrillation refers to the process in which a material forms a fibrous structure with a certain direction and length under the action of external force.
[0083] In a high-speed disperser, the centrifugal force, shear force and impact force generated by the high-speed rotating dispersion disk fully mix the fibers and other components in the material, so that the polymer molecular chains in the material can be stretched and oriented to form a fibrous structure. The high-speed disperser can not only achieve fiberization, but also make the fibers in the material evenly distributed through its mixing and dispersing action, improve the uniformity and performance of the product, and achieve the ideal dispersion and fiberization effect.
[0084] In some embodiments, the negative electrode main material is selected from any one or a combination of at least two of artificial graphite, natural graphite, microcrystalline graphite, soft carbon and hard carbon. Without exceeding the scope of understanding of those skilled in the art, those skilled in the art can freely implement, and the present invention does not impose any limitation on this.
[0085] In some embodiments, the conductive agent is selected from one or more of carbon black, conductive carbon, superconducting carbon, acetylene black, carbon nanotubes, Ketjen black, carbon dots, carbon fibers, graphene, and metal particles. Without exceeding the scope of understanding of those skilled in the art, those skilled in the art may freely implement, and the present invention does not impose any limitation on this.
[0086] The fourth aspect of the present invention provides a lithium-ion battery, which includes the negative electrode sheet provided by the third invention of the present invention, and also includes a positive electrode sheet and a separator.
[0087] The embodiments of the present invention will be described in more detail below through examples and comparative examples, wherein all examples and comparative examples are lithium ion battery sample groups prepared by the same process.
[0088] In order to intuitively and comprehensively reflect the advantages of the technical solution of the present invention, all embodiments and comparative examples were tested as follows:
[0089] Negative electrode wettability test and battery initial performance test.
[0090] Among them, the wettability test of the negative electrode sheet is a test performed before it is assembled into a lithium-ion battery.
[0091] It should be noted that the embodiments of the present invention are not limited to these examples.
[0092] Example 1
[0093] 1. Preparation of composite adhesive
[0094] S1. Add high swelling styrene acrylic emulsion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a folded and solidified mass ratio of 10:90, and connect a high and low temperature constant temperature bath.
[0095] High swelling styrene acrylic emulsion means swelling of 150%, and high molecular PTFE emulsion means molecular weight of 600W.
[0096] The melting point of high swelling styrene acrylic emulsion is 130℃, and the primary particle size of the emulsion is 300nm. The primary particle size of high molecular PTFE emulsion is 200nm.
[0097] S2. Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then heat to 80°C, and continue stirring for 60 minutes.
[0098] S3, after standing for 60 minutes to cool, pass through a 200-mesh sieve, transfer the sieve material to a vacuum drying oven, and dry at 50° C. for 24 hours to obtain the composite adhesive.
[0099] The calculation formula of swelling rate is: Swelling rate (%) = (mass or volume after swelling) / initial mass or volume × 100%
[0100] SEM images of the composite adhesive are shown in Figure 1 shown.
[0101] 2. Preparation of negative electrode sheet
[0102] N1. Add the negative electrode main material graphite and conductive carbon into a planetary stirring tank at a mass ratio of 96:2;
[0103] N2, using a double planetary agitator (5L) at 15°C with a revolution of 20 r / min and a rotation of 50 r / min; stirring for 15 min;
[0104] N3, disperse for 30 minutes to obtain the first mixed material;
[0105] N4, adding the composite adhesive prepared in step 1;
[0106] The mass ratio of the negative electrode main material graphite to the composite binder is 96:2;
[0107] N5, maintaining the tank temperature at 15°C and stirring for 1.5 hours to obtain the second mixed material;
[0108] N6, placing the second mixed material in an oven at 130°C for 1.5 hours;
[0109] N7. The heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;
[0110] N8, through the hot roller mill roll pressing mold and composite into a negative electrode sheet.
[0111] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged.
[0112] The capillary test method is as follows: a. Take the grade sheet (control compaction and surface density) and lay it flat; b. Take the capillary to absorb the electrolyte and record the height of the electrolyte liquid level; c. Place the capillary after the absorption of liquid vertically on the grade sheet; d. Let it stand for 100 seconds to allow the electrolyte to fall freely; e. Record the electrolyte liquid level.
[0113] The data of the height of the electrolyte level falling in the capillary tube in 100 seconds when the electrolyte wettability is tested by the capillary method. The larger the value, the better the wettability.
[0114] 3. Preparation of positive electrode
[0115] 1. The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 ) 2 , a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.
[0116] 4. Preparation of lithium-ion batteries:
[0117] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.
[0118] After the preparation is completed, 20 lithium-ion battery samples are taken for the first efficiency test, and the test results are averaged.
[0119] The test method is as follows:
[0120] The test steps are set by the blue power test system (constant current charging 0.33C (voltage ≥ 4.3V), constant voltage charging (current ≤ 0.02C), standing for 10 minutes; constant current discharge 0.33C (voltage ≤ 2.8V),
[0121] The system reads the first effect.
[0122] Example 2
[0123] 1. Preparation of composite adhesive
[0124] S1. Add high swelling styrene acrylic emulsion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a folded and solidified mass ratio of 1:99, and connect a high and low temperature constant temperature bath.
[0125] High swelling styrene acrylic emulsion swells by 150% and high molecular weight PTFE emulsion has a molecular weight of 600W.
[0126] The melting point of high swelling styrene acrylic emulsion is 130℃, and the primary particle size of the emulsion is 300nm. The primary particle size of high molecular PTFE emulsion is 200nm.
[0127] S2. Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then heat to 80°C, and continue stirring for 60 minutes.
[0128] S3, after standing for 60 minutes to cool, pass through a 200-mesh sieve, transfer the sieve material to a vacuum drying oven, and dry at 50° C. for 24 hours to obtain the composite adhesive.
[0129] 2. Preparation of negative electrode sheet
[0130] N1. Add the negative electrode main material graphite and conductive carbon into a planetary stirring tank at a mass ratio of 96:2;
[0131] N2, using a double planetary agitator (5L) at 15°C with a revolution of 20 r / min and a rotation of 50 r / min; stirring for 15 min;
[0132] N3, disperse for 30 minutes to obtain the first mixed material;
[0133] N4, adding the composite adhesive prepared in step 1;
[0134] The mass ratio of the negative electrode main material graphite to the composite binder is 96:2;
[0135] N5, maintaining the tank temperature at 15°C and stirring for 1.5 hours to obtain the second mixed material;
[0136] N6, placing the second mixed material in an oven at 130°C for 1.5 hours;
[0137] N7. The heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;
[0138] N8, through the hot roller mill roll pressing mold and compound into the negative electrode sheet.
[0139] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.
[0140] 3. Preparation of positive electrode
[0141] 1. The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 ) 2 , a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.
[0142] 4. Preparation of lithium-ion batteries:
[0143] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.
[0144] After the preparation is completed, 20 lithium-ion battery samples are taken for the first efficiency test, and the test results are averaged.
[0145] The testing method is the same as that in Example 1.
[0146] Example 3
[0147] 1. Preparation of composite adhesive
[0148] S1. Add high swelling styrene acrylic emulsion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a folded and solidified mass ratio of 5:95, and connect a high and low temperature constant temperature bath.
[0149] High swelling styrene acrylic emulsion swells by 150% and high molecular weight PTFE emulsion has a molecular weight of 600W.
[0150] The melting point of high swelling styrene acrylic emulsion is 130℃, and the primary particle size of the emulsion is 300nm. The primary particle size of high molecular PTFE emulsion is 200nm.
[0151] S2. Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then heat to 80°C, and continue stirring for 60 minutes.
[0152] S3, after standing for 60 minutes to cool, pass through a 200-mesh sieve, transfer the sieve material to a vacuum drying oven, and dry at 50° C. for 24 hours to obtain the composite adhesive.
[0153] 2. Preparation of negative electrode sheet
[0154] N1. Add the negative electrode main material graphite and conductive carbon into a planetary stirring tank at a mass ratio of 96:2;
[0155] N2, using a double planetary agitator (5L) at 15°C with a revolution of 20 r / min and a rotation of 50 r / min; stirring for 15 min;
[0156] N3, disperse for 30 minutes to obtain the first mixed material;
[0157] N4, adding the composite adhesive prepared in step 1;
[0158] The mass ratio of the negative electrode main material graphite to the composite binder is 96:2;
[0159] N5, maintaining the tank temperature at 15°C and stirring for 1.5 hours to obtain the second mixed material;
[0160] N6, placing the second mixed material in an oven at 130°C for 1.5 hours;
[0161] N7. The heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;
[0162] N8, through the hot roller mill roll pressing mold and compound into the negative electrode sheet.
[0163] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.
[0164] 3. Preparation of positive electrode
[0165] 1. The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 ) 2 , a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.
[0166] 4. Preparation of lithium-ion batteries:
[0167] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.
[0168] After the preparation is completed, 20 lithium-ion battery samples are taken for the first efficiency test, and the test results are averaged.
[0169] The testing method is the same as that in Example 1.
[0170] Comparative Example 1
[0171] 1. Selection of Binder
[0172] In this comparative example, PTFE was selected as the binder.
[0173] 2. Preparation of negative electrode sheet
[0174] N1. Add the negative electrode main material graphite and conductive carbon into a planetary stirring tank at a mass ratio of 96:2;
[0175] N2, using a double planetary agitator (5L) at 15°C with a revolution of 20 r / min and a rotation of 50 r / min; stirring for 15 min;
[0176] N3, disperse for 30 minutes to obtain the first mixed material;
[0177] N4, adding the composite adhesive prepared in step 1;
[0178] The mass ratio of the negative electrode main material graphite to the composite binder is 96:2;
[0179] N5, maintaining the tank temperature at 15°C and stirring for 1.5 hours to obtain the second mixed material;
[0180] N6, placing the second mixed material in an oven at 130°C for 1.5 hours;
[0181] N7. The heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;
[0182] N8, through the hot roller mill roll pressing mold and composite into a negative electrode sheet.
[0183] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.
[0184] 3. Preparation of positive electrode
[0185] 1. The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 ) 2 , a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.
[0186] 4. Preparation of lithium-ion batteries:
[0187] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.
[0188] After the preparation is completed, 20 lithium-ion battery samples are taken for the first efficiency test, and the test results are averaged.
[0189] The testing method is the same as that in Example 1.
[0190] The test results of Examples 1-3 and Comparative Examples are shown in the following table.
[0191] sample Liquid level drop height in 100s / mm First effect / % Example 1 86 87.30 Example 2 9 86.51 Example 3 42 87.04 Comparative Example 1 5 86.35
[0192] According to the above table:
[0193] Compared with Example 1, the composite binder prepared in Example 2 has a lower liquid level drop height in 100 seconds for the negative electrode sheet, and the wettability effect is significantly reduced at this time, and the first-effect performance also has a downward trend.
[0194] Compared with Example 1, the composite binder prepared in Example 3 has a lower liquid level drop in 100 seconds when used for the negative electrode sheet than that in Example 1, and the wettability effect is also inferior to that in Example 1, and the first-effect performance is slightly reduced; however, compared with Example 2, the wettability effect of the negative electrode sheet is significantly improved. This is because the amount of styrene-acrylic emulsion added is increased, and its volume expands in the solvent, so that the electrolyte is fully absorbed, and the negative electrode sheet has excellent wetting performance.
[0195] According to the data of Examples 1-3, if the proportion of high swelling styrene acrylic emulsion is too small, the wetting performance of the composite adhesive will be seriously affected. This confirms that high swelling styrene acrylic emulsion can improve the wettability of the system, and the swelled styrene acrylic may cover part of the PTFE, reducing the effect of PTFE reaction sites.
[0196] According to the comparative examples, the composite binder has obvious advantages over traditional PTFE in terms of wettability of negative electrode sheets and initial performance of prepared lithium-ion batteries.
[0197] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A dry electrode composite binder, characterized in that: It is a mixture of a high swelling styrene acrylic emulsion and a high molecular weight PTFE emulsion; the high swelling styrene acrylic emulsion has a swelling greater than or equal to 100% and the high molecular weight PTFE emulsion has a molecular weight not less than 500W.
2. The adhesive according to claim 1, characterized in that The high swelling styrene acrylic emulsion has a melting point of 100°C to 150°C; The primary particle size of the high swelling styrene acrylic emulsion is less than 500 nm; The primary particle size of the polymer PTFE emulsion is less than 300 nm.
3. A method for preparing the dry electrode composite binder as claimed in claim 1 or 2, characterized in that: The method is prepared by a mixed coprecipitation method of styrene-acrylic emulsion and PTFE emulsion, which specifically comprises the following steps: S1, adding high swelling styrene acrylic emulsion and high molecular weight PTFE emulsion into a container; S2, let stand, then stir; S3, the precipitate obtained after solid-liquid separation is dried in a vacuum drying oven to obtain the composite adhesive.
4. The method according to claim 3, characterized in that: In the step S1, the mass ratio of the high swelling styrene acrylic emulsion to the high molecular weight PTFE emulsion after solidification is (1-10): (90-99).
5. The method according to claim 3, characterized in that: In step S2, the standing time is 40 min to 80 min, the stirring linear speed is 0.8 m / s to 1.5 m / s, and the stirring time is 20 min to 70 min; The stirring is divided into low-temperature stirring and high-temperature stirring. The low-temperature stirring time is 20 minutes to 40 minutes, and the high-temperature stirring time is 30 minutes to 70 minutes.
6. The method according to claim 5, characterized in that The low temperature is 5°C to 20°C, and the high temperature is 60°C to 100°C; Preferably, the low temperature is selected from 13°C to 17°C, and the high temperature is selected from 80°C to 90°C.
7. The method according to claim 3, characterized in that In step S3, the temperature in the vacuum drying oven is 40° C. to 60° C., and the drying time is 12 h to 36 h.
8. A negative electrode sheet comprising the composite binder according to claims 1 to 7, a conductive agent and a negative electrode active material.
9. The negative electrode sheet according to claim 8, characterized in that: The preparation method of the negative electrode sheet is as follows: N1, first add the negative electrode main material and the conductive agent into the planetary stirring tank in a mass ratio of (90-98): (0.5-5); The main material of the negative electrode is graphite, and the conductive agent is conductive carbon; N2, using a double planetary agitator at a temperature of 10℃~18℃, orbiting at 15r / min~25r / min, rotating at 50r / min~100r / min, stirring for 10min~30min; N3, disperse for 30min to 60min to obtain the first mixed material; N4, adding a composite binder to the first mixed material; The mass ratio of the negative electrode main material to the composite binder is (90-98): (0.5-5); N5, maintaining the tank temperature at 10°C to 18°C, stirring for 1h to 2h to obtain the second mixed material; N6, placing the second mixed material in an oven at 90°C to 140°C for 1h to 2h; N7, the heated second mixed material is placed in a high-speed disperser and dispersed for 4 to 6 minutes, at a line speed of 30 m / s to 45 m / s for fiberization; N8, and finally passed through a hot roller pressing mold and composited into a negative electrode sheet.
10. A lithium ion battery comprising the negative electrode sheet, positive electrode sheet, separator and electrolyte according to any one of claims 8 to 9.